Comparative study of Bacillus clausii and multistrain probiotics in the management of acute diarrhoea in children - Hamid, Farzana; Quaium, Syed Moosa M. A.; Rahman, Azizur (International Journal of Research in Medical Sciences, 2019)
Background: Diarrhoea is the second most common cause of under-five mortality especially in developing world. Many studies have been conducted so far using different probiotic strains with variable outcome. So, the aim of the present study was to compare the clinical efficacy of Bacillus clausii and multi strain probiotic formulation as adjunct treatment of acute diarrhoea. Methods: This prospective single blind randomized controlled clinical trial included 300 infants and children between 6 months to 6 years of age admitted in a tertiary care hospital Sylhet, Bangladesh with acute watery diarrhoea having varied dehydration status ranging from no to severe dehydration excluding shocked state. Cases were randomly assigned to three groups which were group I (n=100) comprised of children who were treated with standard treatment (according to WHO guideline) only as control group, group II (n=100) who received standard treatment plus Bacillus clausii and group III (n=100) who received standard treatment plus multi strain probiotic formulation (Lactobacillus casei, Lactobacillus rhamnosus, Lactobacillus acidophilus, Lactobacillus bulgaricus, Bifidobacterium breve, Bifidobacterium infantis, Streptococcus thermophilus). Primary outcome variables were duration, frequency of diarrhoea and consistency of stool. Secondary outcome variable was duration of hospital stay. Results: Mean duration of diarrhoea was significantly shorter (p=0.001) in group III (2.62 days) compared to group I (3.26 days) and group II (3.22 days). Frequency of diarrhoea was significantly lower on day 3 of probiotic administration in group III (p <0.05) and on day 5 of treatment in group II (p <0.05). Stool consistency significantly improved on day 3 in group III (p <0.05) while it was on day 4 in group II. The duration of diarrhoea, hospital stay, stool consistency and frequency of stool on day 3 were not statistically significant (p >0.05) in group II in comparison to group I and group III. Conclusions: Multistrain probiotic formulation is effective in reducing the duration, frequency of diarrhoea and duration of hospital stay.